Antidepressant-like Effect of Fuzi Total Alkaloid on Ovariectomized Mice - Lei Liu; Bingjin Li; Yang Zhou; Liang Wang; Fang Tang; Dongyuan Shao; Xiulan Jiang; Hui Zhao; Ranji Cui; Yuxin Li (Elsevier, 2012)
Recent studies in vivo and vitro have shown that Fuzi polysaccharide has an antidepressant-like effect. Polysaccharide and total alkaloid are the two most important components of Fuzi. However, little is known about the antidepressant-like effect of Fuzi total alkaloid. To investigate the antidepressant-like effect of Fuzi total alkaloid, behavioral studies were performed in the open field test and forced swimming test. Repeated intragastric administration of Fuzi total alkaloid for 7 days (10 mg/kg) to normal mice decreased immobility time compared to the vehicle group. Furthermore, repeated administration of Fuzi total alkaloid (10 or 30 mg/kg) to ovariectomized mice also decreased immobility time in a dose-dependent manner. However, these antidepressant-like behavioral effects were not simply due to locomotor hyperactivity. Further experiments showed that Fuzi total alkaloid enhanced the ratio of phospho-CREB/CREB (cAMP response element-binding) and BDNF (brain-derived neurotrophic factor) protein level in the frontal cortex and hippocampus in ovariectomized mice but not in normal mice. These results indicate that the CREB-BDNF pathway may be involved in the antidepressant-like effect of Fuzi total alkaloid in ovariectomized mice.[Supplementary Figures: available only at http://dx.doi.org/10.1254/jphs.12163FP] Keywords:: alkaloid, ovariectomized mouse, forced swimming, BDNF (brain-derived neurotrophic factor)